HEPATITIS B VIRUS AND RHEUMATIC DISEASES - B. S. Belov; D. T. Abdurakhmanov (Научно-практическая ревматология)
Hepatitis B virus (HBV) is often found and associated with immune-mediated inflammatory rheumatic diseases (IMIRDs), necessitating the modification of both antiviral and antirheumatic therapies. The review provides basic information about the structure of HBV, the course of chronic HBV infection, and the prevention of HBV reactivation in patients with IMIRDs who receive immunosuppressive therapy.